Clinical and Histopathological Study of Important Air-Breathing Fishes - Patwary, ZP; Faruk, MAR; Ali, MM (Progressive Agriculture, 2013)
A study was conducted to know the health and disease problems of three important air-breathing fishes viz. Shing (Heteropneustes fossilis), Magur (Clarias batrachus) and Thai Koi (Anabas testudineus) through clinical and histopathological technique from June 2007 to March 2008 collected from selected farms and from local markets. Generally, during December and January, acute pathologies were recorded. Clinical signs of Shing included haemorrhage, extended belly and ulceration. Histopathologically, partly missing and splitted epidermis and dermis, necrotic, vacuoled and ruptured myotomes of muscle with fungal granuloma were observed. Major gill pathologies included partly missing and highly hypertrophied, haemorrhagic gill lamellae, presence of monogenetic trematode and pyknotic cells. In liver, haemorrhagic areas, necrotic, vacuoled, hyperplasid hepatocytes, cell debris, pyknotic nuclei and plenty of inflammatory cells were evident. Haemorrhages, vacuolation, necrosis, missing and ruptured kidney tubules and pyknotic nuclei were the major pathologies of kidney. Clinically, dark red lesion, haemorrhage, necrosis and ulcer in body surface were seen in Magur. Histopathologically observed pathologies in Magur were almost similar to that of Shing. Clinical signs of Thai Koi included discoloration, loss of scales and fins, abnormal caudal fin, haemorrhage in gill and ulcer. Marked histopathology in the skin and muscle were observed such as totally lost epidermis, dermis separated from muscle, severely ruptured, degenerated and missing of myotomes in many places. In gills, hypertrophy, hyperplasia, telangiectasis, clubbing, haemorrhage and massive necrosis in both primary and secondary gill lamellae were found. Pathologies observed in liver and kidney were most alike to that of Shing. In the months of February and March, all the investigated organs of the three fish species were at a healing stage. DOI: http://dx.doi.org/10.3329/pa.v19i1.17109 Progress. Agric. 19(1): 69 - 78, 2008